EFEKTIFITAS KOTAK PERANGKAP NYAMUK DALAM PENGENDALIAN NYAMUK Aedesaegypti - Aienieng Nurahayati; Sayono S (Universitas Muhammadiyah Semarang, 2015)
Background: Kalongan Village, Semarang regency, Hamlet Fur RT 04 and 05 RW 06 is endemic Dengue Hemorrhagic Fever ( DHF ) from data obtained from the Department of Health Unggaran East. Efforts to prevent this disease rely on vector control using insecticide-treated mosquito trap box malathion.Objective: Determinethe effectiveness of mosquito trap box in the residential neighborhood.Method: This explanatory research using quasi-experimental design, the post-test only design. The study population was 32 houses in the hamlet Fur RT 04 and 05 RW 06, sample research homes around the latest dengue patients in May 2014 in the Village Kalongan within a radius of 100 meters. Independent variables include the dose of insecticide and the dependent variable is the number of mosquito landed and died. Data were analyzed using the Mann Whitney test.Results:The number of mosquito landed ranged from 0 s / d 5, with a mean of 0.52 and standard deviation 0.836. The number of mosquito landed on the box containing malathion 0.50 g/m2 range 65 tail, with a mean of 0.58 and standard deviation of 0.965, while the box containing malathion 0.75 g/m2 range from 51 tail with a mean of 0.46 and standard deviation 0.683 ; did not differ significantly (p = 0.822). The number of dead mosquitoes ranged from 0 s / d 3, with a mean of 0.05 and standard deviation 0.272. The number of dead mosquitoes on the box containing malathion 0.50 g/m2 range from 1 tail with a mean of 0.01 and a standard deviation of 0.094, while the malathion dose of 0.75 g/m2 range from 10 cows with mean 0.09 and standard deviation 0.369, different significantly (p = 0.017).Conclusion: There is no difference in the number of mosquitoes that land on both doses of malathion. There is a difference in the number of dead mosquitoes at both doses of malathion.